Modeling and Processing L-Band Ground Based Radar Data for Landslides Early Warning - A. R. Laganà; M. T. Bevacqua; T. Isernia (Journal of Electrical and Computer Engineering)
L-band radars have been proposed as possible way for monitoring landslides. In this paper, we examine and solve the principal difficulties arising in modeling and processing radar data, evidencing differences with more usual SAR imaging. Numerical examples in support of the proposed processing procedure are finally provided.